Socio-Linguistic Referential Construction of Leaders in Kenya’s 2008 Post-Consultation Discourse: Coalition Governance in Nascent Democracies - Khasandi, Vicky Inviolata; Telewa, Vicky Khasandi; Ndambuki, Jacinta M. (Advances in Social Sciences Research Journal, 2016)
The general objective of this research was to gain understanding of the discursive referential construction. The paper aimed to enhance the existing studies on political discourse by investigating referential strategies used to institutionalise ideologies in coalition governments in nascent democracies. The objective of the study was to define referential strategies employed by Mwai Kibaki and Raila Odinga as principals in Kenya’s 2008 coalition government and to construct and negotiate their ideological perspectives in governance. Four written texts were purposively sampled and accessed from the electronic data searches. The study was anchored on Critical Discourse Analysis approach. The results indicated that linguistic choices are ideologically and politically motivated in a consistent process of representation.